Titanium-based Additives for Dental Polymer Composites - Nidal W. Elshereksi; Mariyam J. Ghazali; Andanastuti Muchtar; Che H. Azhari (Advanced Aspects of Engineering Research Vol. 2, 2021)
Poly(methyl methacrylate) (PMMA) is broadly employed in dental technology due to its easy handling, exceptional appearance, lack of toxicity and biocompatibility. However, this material as an ideal dental base is still restricted by a few limitations such as poor strength and radiopacity. Attempts to improve the mechanical and radiopacity properties of denture base materials through the inclusion of silica-based fillers are ongoing. Although silanated silica-based fillers are frequently exploited, they are not adequately strong. They also exhibit cracks, which either cut through the glass fillers or propagate around the filler particles. Such deficiency occurs when the dental composites are placed in the aqueous oral environment because of the hydrolytic degradation of siliceous fillers and silane-coupling agents. The clinical problem of using silanes in adhesion promotion is bond degradation over time in the oral environment. Moreover, silanes do not bond efficiently to nonsilica-based dental restorative composites. Therefore, the selection of suitable materials is very important to obtain better compatibility among the composites’ phases leading to the promotion of the resultant materials’ longevity. This chapter presents titanium-based fillers as alternatives to siliceous fillers. It includes PMMA composite as a denture base, Interfacial phase and coupling agents, Titanium-based fillers in prosthetic dentistry, Titanate-treated titanium-based fillers. Titanates are found to be effective couplers in treating Ti-based fillers because of their chemical compatibility and relatively high stability in a humid environment.